Chemerin15-Ameliorated Cardiac Ischemia-Reperfusion Injury Is Associated with the Induction of Alternatively Activated Macrophages - Chao Chang; Qingwei Ji; Bangwei Wu; Kunwu Yu; Qiutang Zeng; Shuanli Xin; Jixiang Liu; Yujie Zhou (Mediators of Inflammation)
Chemerin15 (C15), an endogenous anti-inflammatory component, inhibits the activity of neutrophils and macrophages through G protein-coupled receptor ChemR23; however, its role as well as functional mechanism in mouse myocardial ischemia/reperfusion (I/R) injury remains unknown. Methods. Sham or I/R operations were performed on C57BL/6J mice. The I/R mice received an injection of C15 immediately before reperfusion. Serum troponin T levels, infarct size, cardiomyocyte apoptosis, reactive oxygen species (ROS) production, and infiltration of neutrophils were assessed 24 h after reperfusion, while the macrophage phenotypes, macrophage infiltration, and inflammatory cytokine levels were assessed 48 h after reperfusion. Results. Compared with the control group, the C15-treated mice showed an obvious amelioration of I/R injury and displayed less ROS, accompanied by reduced neutrophil recruitment. C15 decreased the tumor necrosis factor- (TNF-) α and interleukin- (IL-) 6 levels and increased the IL-10 levels in the serum of the I/R mice, which suggested a suppressed inflammatory response that could be related to elevated alternatively activated M2 macrophages with characteristic skewed expression of M2 markers and inhibition of classically activated M1 marker expression. Conclusion. C15 may induce alternatively activated M2 macrophage polarization and suppress the inflammatory response to protect against myocardial I/R injury in mice.